2019
DOI: 10.20511/pyr2019.v7n1.261
|View full text |Cite
|
Sign up to set email alerts
|

Acción tutorial para el desarrollo de las habilidades sociales en estudiantes universitarios

Abstract: <p>La presente investigación se realizó con el propósito de diseñar talleres de tutoría en la atención de habilidades sociales poco desarrolladas de estudiantes universitarios; a través de las cuales manifiestan sus necesidades, sentimientos, preferencias, opiniones y derechos, respetando a los demás y como consecuencia se visualiza el autoreforzamiento y maximiza la probabilidad de conseguir refuerzo externo. El estudio fue abordado desde el paradigma interpretativo, enfoque cualitativo, el método proye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Correlation between the tutoring system and the academic performance of students The results of the research show a high positive correlation between the variables analyzed, these coincide with the statements of Araneda-Guirriman et al ( 2020), who previously highlighted the relationship between tutoring and tutorial periodicity with educational performance. Furthermore, they agree with the research of Javier et al (2019), who demonstrated that tutoring is linked to educational performance, emphasizing the importance of tutors not having an excessive workload. On the other hand, the studies by Sucari et al (2021) and Zuniga et al (2018) reinforce these findings by indicating that those students who achieve outstanding academic performance have a greater probability of graduating.…”
Section: Tablesupporting
confidence: 87%
See 1 more Smart Citation
“…Correlation between the tutoring system and the academic performance of students The results of the research show a high positive correlation between the variables analyzed, these coincide with the statements of Araneda-Guirriman et al ( 2020), who previously highlighted the relationship between tutoring and tutorial periodicity with educational performance. Furthermore, they agree with the research of Javier et al (2019), who demonstrated that tutoring is linked to educational performance, emphasizing the importance of tutors not having an excessive workload. On the other hand, the studies by Sucari et al (2021) and Zuniga et al (2018) reinforce these findings by indicating that those students who achieve outstanding academic performance have a greater probability of graduating.…”
Section: Tablesupporting
confidence: 87%
“…Tutoring and tutorial periodicity are eloquently related to educational performance, but it is essential that tutors do not have an excessive workload (Araneda-Guirriman et al, 2020;Javier et al, 2019). In addition, tutoring is shown as a valuable resource to solve academic doubts and improve study skills (Martínez et al, 2017).…”
mentioning
confidence: 99%
“…La tutoría y la periodicidad tutorial se relacionan elocuentemente con el rendimiento educativo, pero es esencial que los tutores no tengan una carga laboral excesiva (Araneda-Guirriman et al, 2020;Javier et al, 2019). Además, la tutoría se muestra como un recurso valioso para resolver dudas académicas y mejorar habilidades de estudio (Martínez et al, 2017).…”
Section: Introductionunclassified
“…Se ha encontrado que en Latinoamérica se han realizado estudios sobre habilidades sociales con personas universitarias, como el de Javier Napa et al (2019), quienes se han orientado a operar programas para complementar el perfil profesional. Así como a indagar si existen diferencias de género (García Terán et al, 2014).…”
unclassified